Nursing empathy and the context of the nurse-patient relationship: critical considerations - Leandro Felipe Mufato; Maria Aparecida Munhoz Gaíva (Universidad de Alicante, 2019)
Empathy is an ability to understand the other, fundamental in the nurse-patient relationship. In nursing, Theresa Wiseman formulated her own concepts about empathy from the characteristics of the profession. However, after more than ten years of the empathy concept in nursing formulated by the author, we have to observe the current context of occurrence of this phenomenon: the nurse-patient relationship. In this essay, we have looked at some factors that demonstrate the importance of empathy between nurses and patients, as well as what challenges the profession faces to promote its autonomy and which directly interfere with the way nurses occupy space in relation to their patients and consequently in the development of empathy. Nursing work in wards, the division of labor with technicians and submission of the profession to the modes of production of hospital care are presented as aspects that interfere in the nurse-patient relationship and in empathy. It is concluded that there is a need to resume individualized care actions in the direct relationship with patients, so that the nurse can be seen as a resource, as a source of care for patients.